Pengaruh Perputaran Modal Kerja, Perputaran Aset dan Efektivitas Penggunaan Dana terhadap Laba Bersih - Eko Prasetyo (Pusat P2M Politeknik Negeri Batam, 2017)
Profit is one of the information contained in the financial statements of a company that is very important for the internal and external parties to make a decision. There are three decisions taken by the financial management, namely investment decisions, spending decisions or funding (financing decision), and the policy of distribution of dividends to shareholders (devident policy). Investment and financing decision can be found reflection in the balance sheet. Fund is one financial concept common to refer to the resources realized by the company. Effective use of funds can be determined by using financial ratio is the ratio of the activity. Which includes ativitas ratio is the ratio of working capital turnover, fixed asset turnover ratio, and the ratio of total asset turnover. Banking company is a company engaged in the financial sector, type of research is descriptive quantitative research. The population in this study are all banking companies listed in Indonesia Stock Exchange (BEI) in the period of 2013 and 2014 as many as 20 companies. This analytical tool used to determine the effect of working capital turnover, fixed asset turnover, and turnover of assets to the banking company's net profit by using multiple linear regression. The results showed that there is no influence the effectiveness of the use of funds to net income at the banking company on the stock exchange.